Long‐Term Pain Reduction Does Not Imply Improved Functional Outcome in Patients Treated With Combined Supraorbital and Occipital Nerve Stimulation for Chronic Migraine. Issue 5 (10th February 2016) - Clark, Shannon W.; Wu, Chengyuan; Boorman, David W.; Chalouhi, Nohra; Zanaty, Mario; Oshinsky, Michael; Young, William B.; Silberstein, Stephen D.; Sharan, Ashwini D.
Abstract : Background: Dual supraorbital and occipital nerve stimulation (SONS and ONS) have shown promising efficacy in treating primary headaches. However, its functional outcome is not well studied. Objective: To present functional outcome studies of combined SONS and ONS for chronic migraine using verified metrics. Method: Consecutive patients with both SONS and ONS assessed with Migraine Disability Assessment (MIDAS) and Beck Depression Index (BDI) both preoperatively and postoperatively were studied. Selected predictor variables included patients with ≥50% improvement of pain, disability status, number of years from diagnosis to implantation, and narcotic use. Functional outcome variables included net improvement of ranked MIDAS and BDI scores. Multivariate analysis of variance was performed to assess the correlation between the outcome and predictor variables. Results: Sixteen patients (12 female; average age 52 years old) were studied. Follow‐up ranged from 5 to 80 months (average 44.5; σ  = 21.4 months). At most recent follow‐up, eight patients had a positive response (≥50% improvement in headache), which was the only predictor of functional outcome (total MIDAS, MIDAS‐B, and BDI) ( p  = 0.021). Of note, improvement in functional outcome was only significant during the perioperative 3–6 months period and not throughout long‐term follow‐up. Among the predictor variables, a strong inverse correlation was found between disability status and positive response to stimulation ( r  = −0.582). Conclusion: There is a paucity of studies in quality of life, productivity, and psychosocial aspects with peripheral nerve stimulation therapy for headache. Patients with a positive response to SONS and ONS also reported overall improvement in their functional status as reflected by MIDAS and BDI in the perioperative period. Unfortunately, this effect waned over the long‐term follow‐up.